2022
DOI: 10.1111/eip.13274
|View full text |Cite
|
Sign up to set email alerts
|

An online intervention for 18–25‐year‐old youth whose parents have a mental illness and/or substance use disorder: A pilot randomized controlled trial

Abstract: Aim: Young adults aged 18-25 whose parents have a mental illness or substance use problem can be vulnerable to multiple difficulties in adulthood. There are, however, few available interventions designed for this group. This study evaluated a 6 week online intervention (mi. spot; mental illness: supported, preventative, online, targeted) specifically designed for this population. The intervention aims to improve mental health and wellbeing.Methods: Forty-one young people, recruited from the community, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Two studies measured mental health literacy [ 31 , 32 ], two studies measured help-seeking intentions/attitudes [ 33 , 34 ], one study measured mental health literacy and help-seeking intentions/attitudes [ 35 ], one study measured mental health literacy and stigma [ 36 ], and four studies(one of the studies has two separate reports) measured help-seeking intentions/attitudes and stigma [ 37 39 ]. Of the 10 final full-text studies, 5 studies in Australia, two studies in the United States of America, one study in Ethiopia, one study in Singapore, and one study in the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies measured mental health literacy [ 31 , 32 ], two studies measured help-seeking intentions/attitudes [ 33 , 34 ], one study measured mental health literacy and help-seeking intentions/attitudes [ 35 ], one study measured mental health literacy and stigma [ 36 ], and four studies(one of the studies has two separate reports) measured help-seeking intentions/attitudes and stigma [ 37 39 ]. Of the 10 final full-text studies, 5 studies in Australia, two studies in the United States of America, one study in Ethiopia, one study in Singapore, and one study in the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the risk of bias assessment are shown in in supplementary material 2. The table shows that three studies [ 31 , 35 , 38 ] are excellent, four are good [ 33 , 34 , 36 , 37 ], and two are low in quality [ 32 , 39 ]. The studies that have excellent or good quality are clear about their research aim/s, research setting and target population, and study design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sweden, 2 other programs with inconclusive treatment effects have been tested that target significant others and their children [ 37 , 38 ]. Finally, a digital intervention developed in Australia for 18- to 25-year-old individuals with parents with mental illness or substance use disorder [ 36 ] was tested in a pilot study demonstrating positive findings [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the definition varies across the literature, some research studies have defined young adults as those aged 18 to 25 years due to their unique psychosocial and health needs, and the major transitions they undergo from adolescence to adulthood. [17][18][19] Regarding hand hygiene, previously published research have found self-reported hand hygiene to be lower among young adults compared to other age demographics. [20][21][22] Moreover, young adults have reported lower intentions to practice handwashing compared to other age groups 23 ; young adults aged 18 to 29 had a lower frequency of washing and sanitizing hands compared to other age groups 10,24 ; and there is evidence to support these behaviors were similar prior to the pandemic suggesting this demographic is unique and young adults face additional barriers to hand hygiene.…”
Section: Introductionmentioning
confidence: 99%